Skellet mellem folkekirke og frikirke: belyst ud fra grundtvigske frimenigheder i 1880’eme - Trock, Carl (Kirkehistoriske Samlinger, 1994)
On January 4th, 1884, the Ministry of Culture (the Ministry of Church and Education) in a circular letter further stressed the distinction between the National Church (Folkekirken) and the first Grundtvigian free congregations (Frimenighederne) formed in 1883: Wedding ceremonies by the vicars of the National Church had civil validity. The vicars of the free congregations in their churches could only bless marriages which had been previously contracted with the civil authorities. The circular letter was supposed to prevent attempts at evasions. The Grundtvigian church movement on its part had stressed the community no matter whether the congregations were part of or outside the National Church. They had the same spiritual background. It clearly had claimed the connection when the elective congregation at Mors early in 1883 was excluded from the National Church because it willfully had taken liberties in its congregational life. The same year two other congregations decided that they did not want the recognition of the Ministry as free congregations. They wished to be free without seeing themselves as having resigned from the National Church. But in February 1883 the Ministry had determined that baptism in the free congregations was to be regarded only as naming and that wedding ceremonies there had no civil validity. This paper shows from enquiries about the free congregations how unprepared the Ministry of Culture was and how slowly and only occasionally decisions were taken. It also demonstrates how difficult it was to draw dividing lines even in parishes of manageable size. The free congregations were not denied the use of the church yards they had, but at burials at the church yards of the National Church the vicars of the free congrations were almost not allowed to do anything. Not until two and a half years after the the first congregation had been excluded from the National Church, did the Ministry - acting on an enquiry - decided that parents who had their children baptized in the free congregational churches had set themselves apart from the National Church. But those who were godfathers or godmothers at baptisms there could still be considered to be members of the National Church. Free schools (Friskoler), established and maintained by the parents, had appeared as part ofthe Grundtvigian movement. Where free congregations existed, the free school teachers normally belonged there. In that case - the Ministry decided on Oct. 8, 1887 - parents who were members of the National Church were not entitled to “let their children be taught in the free schools”. This decision gave growth to the free congregations, whereas the vicars who locally supervised the educational system dared not take extensive consequences of this. The following year the Ministry had to moderate the decision to the effect that only the exams in religion for the children from the National Church were not allowed to take place in the free schools but at places which the vicars found suitable. Throughout the 1880’es it was attempted to establish a uniform practise. But the distinction that the Ministry wanted to maintain the Grundtvigians tried to delete - and in public opinion they won. The public did not see any differences between the Grundtvigians inside and outside the National Church. But the vicars did. They felt themselves to be pressed in parishes where the free congregations were strong and they did not appeal in vain to the bishops for support. The conflict could be felt as bitter and long for all parties.